Open schooling and pedagogical learning practices articulated with the CONNECT project in basic education (Research, Society and Development, 2022)
The present study aimed to develop pedagogical practices of learning with scientific actions in the perspective of open schooling in basic education through the CONNECT project. Open schooling emphasizes scientific knowledge in the formation of citizens through the areas of science, research, and innovation to promote the quality of life and the well-being of society, articulated with the creation of innovative, interactive, integrated, and inclusive pedagogical practices. The CONNECT project presents its methodology based on scientific actions: care – know – do, with a focus oriented towards future scenarios. The qualitative research methodology with a participatory approach had data collection in a state school in Santa Catarina and in an NGO in Vila Torres, in Curitiba. From the results obtained, it was possible to perceive that the research reveals teaching and learning processes through an educational practice based on the connection between the areas of knowledge that allowed the construction of differentiated pedagogical practices of open schooling. It is important to rethink pedagogical practices with scientific actions in a significant and innovative way, articulating areas of knowledge relevant to the reality of students. The present investigation brings the perspective of open schooling that allows the student to be the protagonist and subject of scientific production through project-based learning.